Erlotinib plus bevacizumab vs erlotinib monotherapy as first-line treatment for advanced EGFR mutation-positive non-squamous non-small-cell lung cancer: Survival follow-up results of the randomized JO25567 study. (January 2021) - Yamamoto, N.; Seto, T.; Nishio, M.; Goto, K.; Yamamoto, N.; Okamoto, I.; Yamanaka, T.; Tanaka, M.; Takahashi, K.; Fukuoka, M.
Highlights: First long-term OS data of erlotinib + bevacizumab vs erlotinib in this population. Both treatment arms showed a similar median OS of approximately 4 years. Results of EGFR and VEGF inhibitor combination therapies are eagerly awaited. Abstract: Objectives: The JO25567 randomized Phase II study demonstrated a statistically significant progression-free survival (PFS) benefit with erlotinib plus bevacizumab compared with erlotinib monotherapy in chemotherapy-naïve Japanese patients with epidermal growth factor receptor mutation-positive ( EGFR +) non-small-cell lung cancer (NSCLC). Here we present updated PFS and final overall survival (OS) data after a median follow-up of 34.7 months. Materials and methods: Patients with stage IIIB/IV or postoperative recurrent NSCLC were randomized to receive oral erlotinib 150 mg once daily ( n = 77) or erlotinib in combination with intravenous bevacizumab 15 mg/kg every 21 days ( n = 75) until disease progression or unacceptable toxicity. OS was analyzed using an unstratified Cox proportional hazards model. Results: Consistent with the primary analysis, addition of bevacizumab to erlotinib was associated with a significant improvement in PFS (hazard ratio [HR] 0.52; 95 % confidence interval [CI]: 0.35–0.76; log-rank two-sided P = 0.0005; median 16.4 months vs 9.8 months, respectively). In contrast, a significant improvement in OS was not seen (HR 0.81; 95 % CI, 0.53–1.23; P = 0.3267; median 47.0 months vs 47.4 months, respectively). Post-study therapy was similar between the treatment arms and EGFR mutation type did not affect OS outcomes. The 5-year OS rate was numerically higher with erlotinib plus bevacizumab vs erlotinib monotherapy (41 % vs 35 %). Updated safety analyses confirmed the previously reported manageable tolerability profile, with no new safety issues. Conclusion: Addition of bevacizumab to first-line erlotinib did not show significant improvement in OS in Japanese patients with stage IIIB/IV or postoperative recurrent EGFR + NSCLC. Both treatment arms showed a similar median OS benefit (as long as 4 years), irrespective of individual patient characteristics. Results from ongoing studies evaluating the combination of EGFR and VEGF signaling inhibitors are eagerly awaited. Trial registration: JapicCTI-111390 and JapicCTI-142569.